(untitled) (JURNAL ADMINISTRASI PUBLIK, 2019)
This study aims to analyze the performance of Ombudsman Republic of Indonesia representative of North Sulawesi Province in the completion of public reports. The authors use the theory of Agus Dwiyanto about measuring organizational performance based on 3 of the 5 indicators, namely productivity, responsiveness, and responsibility. This study used a descriptive with a qualitative approach. Primary data from this study came from interviews, and the secondary data is document tracking. Data collection techniques are interviews, observation, and documentation. Data analysis techniques use data reduction, data presentation, conclusion and verification. The technique of checking the validity of data using triangulation. The result of this study showed that the performance of Ombudsman Republic of Indonesia representative of North Sulawesi Province from the productivity indicator has been running optimally seen from the achievement of the target of completion of the public report even though not supported by adecuate resource. Performance from the responsiveness indicator in terms of increasing public participation by forming networks called â€œKawanua Ombudsmanâ€ has not gone well, while in responding to public reports it has been going well. Performance from the responsibility indicator has been running optimally by following step by step in according to the existing rules. Keywords : Organizational Performance, Ombudsman